MEKANISME PENGAWASAN PEMBIAYAAN MURABAHAH SEBAGAI UPAYA MEMINIMALISIR PEMBIAYAAN BERMASALAH PADA PT. BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU (KCP) TAKENGON - Panetir Bungkes; Milda Sahyuli (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2021)
Minimizing financing problems PT. Bank Syariah Mandiri Sub-Branch Office (KCP) Takengon needs to supervise murabahah financing, be it supervision before financing or supervision after financing. Because most of the assets of PT. Bank Syariah Mandiri KCP Takengon is in murabahah financing with a total of 1388 financing customers so that the quality of the financing must be maintained. This research method uses a qualitative descriptive approach. The data sources that the authors use are primary sources. Data collection techniques obtained from observation, interviews, and documentation. In addition, data analysis used is data reduction, data presentation and drawing conclusions. The result of this research is that the supervision mechanism of murabahah financing at PT. Bank Syariah Mandiri KCP Takengon uses character analysis, capital, capacity, collateral, and conditions of economy (5C). Meanwhile, the cause of problematic financing is due to internal factors and external factors. Furthermore, problematic financing can be minimized through the 5C analysis process unless it is caused by a natural disaster that is beyond the estimation of PT. Bank Syariah Mandiri KCP Takengon. The conclusion of the researcher is that the PT. Bank Syariah Mandiri KCP Takengon has implemented all murabahah financing supervision procedures that have been arranged systematically and structured.